Consumo de alimentos entre adolescentes de comunidades pesqueiras do Rio Grande do Norte(RN) - Liberalino, Laura Camila Pereira (2011)
Food consumption is an indirect method of evaluation of the nutritional status and may contributes as a previous indication for nutritional interventions on public health as well as provide support for national policies on food and nutrition. Dietary practices and inadequate food consumption at the age of childhood and adolescence may be related to the great probability of morbidity and mortality by non-transmittable chronicles diseases in the adult age. The aim of this study was to identify the feeding practices and evaluate the dietary consumption by adolescents in the fishing communities of Rio Grande do Norte, in an attempt to verify its nutritional (un)safety, as well knowing the energy intake, analyze possible associations between inappropriate macronutrients with gender and age, estimates the prevalence of inadequate intake of micronutrients and identify feeding practices around the consumption of fish. This is a cross-sectional study with 201 adolescents aged from 10 to 19 years old in fishing communities in the city of Macau RN, 2008. Dietary practices related to fish consumption were identified by structured questionnaire. The food consumption was obtained by 24 hour recall, with the aid of a photographic record of food and utensils. Dietary intake information was adjusted by the interpersonal and intrapersonal variances, according to Iowa State University. To estimates the total energy consumption by the adolescents we ve used the equation of Estimated Energy Requirement (EER). The analysis of carbohydrates, proteins, vitamins and minerals like phosphorus, magnesium, zinc and iron, was provided by the Estimated Average Requirements (EAR); fiber, calcium and sodium analysis by Adequate Intake (AI); the total lipids by the Acceptable Macronutrient Distribution Ranges (AMDR); and the content and quality of fats by the recommendations of the American Academy of Pediatrics. Descriptive statistics and differences between medians were verified by the Kruskal-Wallis test. To detect associations between variables we ve used the prevalence ratio (IC95%), the Mantel-Haenszel (p-value < 0.05) and multiple logistic regressions between selected nutrients and gender and age variables. The age distribution was predominantly masculine (59.2%) in the range from 10 to 13 years old (70.1%). Fry was the most used way of preparation of the fish (76.8% for fish and 46.1% for seafood), with average per capita consumptions of 94g. The higher prevalence of inadequacy was the excessive consumption of lipids (girls: 47.6%; boys: 26,0%; RP=1.95; IC95% from 1.25 to 3.04) and saturated fatty acids (girls: 24.4%; boys: 10.1%; RP=2.42; IC95% from 1.25 to 4.67). The adolescents from age of 14 to 18 years old had 3.05 (IC95% from 1.35 to 6.93) times the probability to consume saturated fatty acids over the recommendations than adolescents from 10 to 13 years old. Most inadequate prevalence for micronutrients with inferior consumption was of phosphorus among feminine gender (80%) and magnesium among masculine gender (98%). Inadequate prevalence of total lipids and high saturated fatty acids in girls and 14-18 years old adolescents may represents a previous indication for the development of non-transmittable chronicles diseases in that population. The exposure to nutritional unsafety present in significant section of macronutrients and micronutrients may provide elements for the control of adequate intake control, and nutritional disturbance and non-transmittable chronic diseases preventions among adolescents of Ponta do Tubarão State Sustainable Development Reserve, Macau, RN (Brazil).